Fabrication of protein microarrays for alpha fetoprotein detection by using a rapid photo-immobilization process - Sirasa Yodmongkol; Boonsong Sutapun; Verayuth Praphanphoj; Toemsak Srikhirin; Thomas Brandstetter; Jürgen Rühe (Sensing and Bio-Sensing Research, 2016)
In this study, protein microarrays based on sandwich immunoassays are generated to quantify the amount of alpha fetoprotein (AFP) in blood serum. For chip generation a mixture of capture antibody and a photoactive copolymer consisting of N,N-dimethylacrylamide (DMAA), methacryloyloxy benzophenone (MaBP), and Na-4-styrenesulfonate (SSNa) was spotted onto unmodified polymethyl methacrylate (PMMA) substrates. Subsequently to printing of the microarray, the polymer and protein were photochemically cross-linked and the forming, biofunctionalized hydrogels simultaneously bound to the chip surface by short UV- irradiation. The obtained biochip was incubated with AFP antigen, followed by biotinylated AFP antibody and streptavidin-Cy5 and the fluorescence signal read-out. The developed microarray biochip covers the range of AFP in serum samples such as maternal serum in the range of 5 and 100 ng/ml. The chip production process is based on a fast and simple immobilization process, which can be applied to conventional plastic surfaces. Therefore, this protein microarray production process is a promising method to fabricate biochips for AFP screening processes. Keywords: Photo-immobilization, Protein microarray, Alpha fetoprotein, Hydrogel, 3D surface, Down syndrome